Diversity of Bird Species in the Mangrove Forest of the Karang Gading Wildlife Sanctuary and Northeast Langkat - Doly, Raja; Hutasuhut, Melfa Aisyah; Idami, Zahratul (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
Birds play an important role in mangrove ecosystems because they help improve forests in natural ways such as flower pollination, and grain dispersal. This study was conducted to find out the types of birds, diversity, equality and dominance of bird species in the Karang Gading and Langkat Northeast Wildlife Sanctuaries. A method that combines the calculation point of IPA (Indices Ponctuele d'Abundance) with the transect line (line transect). Found 43 species of birds from 10 Orders and 22 families. The diversity index in the Karang Gading and Langkat Northeast Wildlife Sanctuary area has a value of 2.80 with a medium category. Furthermore, the equality index has a value of 0.81 with an uneven category. Then the dominant index of bird species in the area has an average category of non-dominant bird species. This value indicates that the Karang Gading Wildlife Sanctuary and Northeast langkat area supports as a bird habitat with the success of a type of bird in utilizing niches and being able to adapt to environmental conditions from all disturbances such as anthropogenic activities in the region.